Implementation of Benchmarking Concept in Manufacturing Industry of Bangladesh (Global Journal of Management and Business Research, 2018)
Customers nowadays constantly demand for higher quality, shorter lead times and customization of products at a competitive price. Benchmarking might be a way of measuring a firm's strategies and performance against "best-in-class" firms both inside and outside the industry. The purpose of this paper is to investigate the implementation of benchmarking concept in the manufacturing companies in Bangladesh. Existing literatures and some real life examples of benchmarking implementation in different companies are using for the further study. Study found that seven major stages of the benchmarking process independently pay attention to a specific area, which will add value to the process. Various opportunities like benchmarking opens up organizations to new methods, ideas, and tools to improve their effectiveness for help to solve the problems within organizations. Direction and recommendation for implementation of benchmarking are also given.
Keywords: quality; lead times; customization; benchmarking process; opportunities; bangladesh